Cevap:
Lütfen aşağıya bakın.
Açıklama:
let 1. + costheta + isintheta = r (cosalpha + isinalpha) #, İşte # R = sqrt ((1 + costheta) ^ 2 + sin ^ 2teta) = sqrt (2 + 2costheta) #
= #sqrt (2 + 4cos ^ 2 (teta / 2) -2) = 2cos (teta / 2) #
ve # Tanalpha = sintheta / (1 + costheta) == (2sin (teta / 2) cos (teta / 2)) / (2cos ^ 2 (teta / 2)) açık kahve renkli (teta / 2) # = veya # Alfa = teta / 2 #
sonra 1. + costheta-isintheta = r (cos (alfa) + isin (alfa)) = R (cosalpha-isinalpha) #
ve yazabiliriz # (1 + costheta + isintheta) ^ n + (1 + costheta-isintheta) ^ n # DE MOivre teoremini kullanarak
# R ^ n (cosnalpha + isinnalpha + cosnalpha-isinnalpha) #
= # 2r ^ ncosnalpha #
= 2. * 2 ^ astsubaylardır ^ n (teta / 2) cos ((ntheta) / 2) #
= 2. ^ (n + 1) cos ^ n (teta / 2) cos ((ntheta) / 2) #